Reconstructing Intellectual Capital through Islamic Religiosity - Prakoso, Aryo; Ludigdo, Unti; Purwanti, Lilik; ., Roekhudin (KnE Social Sciences, 2023)
Current technological developments have shifted the industrial world from a capitalintensive to a knowledge-based industry. We often find that companies have been awarded higher market value than their book value. Various researchers believe this honor that is given by society to be intellectual capital. Unfortunately, different intellectual ideas presented are still dry, materialistic, secularistic, and far from religious values. This research explained how to reconstruct Intellectual Capital through Islamic spirituality with the method of spirituality through the dimensions of the foundations of Islam. In the spiritualism paradigm, high spiritual norms of faith, good deeds, and noble morals become the foothold. The results of this study produce human capital Rahmatan Lil Alamin which runs full of faith and piety, and structure capital, which is to form an administrative building and run the company not only for profit motives but to provide human benefits by carrying out Sharia principles. Relational capital will be in the form of habluminallah and habluminannas, namely developing and strengthening corporate relationships internally in the company and with stakeholders, shareholders, and society and nature with the principle of amaliyah and providing Value towards Godhead. Keywords: Intellectual Capital, Relational Capital, human, Structure, Islamic Religiousity